Pengaruh Dukungan Suami Terhadap Keberhasilan Menyusui Pada Ibu Post Partum Di Ruang Nifas Rumah Sakit Dr R Soeharsono Banjarmasin - Sri Jamilah; Sri Purwanti Ariani (CV. ITTC INDONESIA, 2024)
Childbirth is a normal physiological event experienced by every woman, characterized by uterine contractions and the delivery of a full-term baby (37-42 weeks) through the vagina, resulting from the fertilization of the egg inside the uterus, either through the birth canal or through other means such as a cesarean section. Childbirth is a natural process that involves the dilation of the cervix, the birth of the baby and placenta from the mother's uterus. There are four stages of childbirth: dilation, delivery of the baby, delivery of the placenta, and finally, the recovery and postpartum observation. There are two types of childbirth: vaginal delivery (also known as normal delivery) where the baby is delivered through the vagina, and cesarean section (C-section) which is a surgical procedure where the baby is delivered through an incision in the abdominal wall (laparotomy) and the uterus, with the condition that the uterus is intact and the fetal weight is over 500 grams. Childbirth is a physiological process that can cause significant changes in the mother's body, allowing the baby to be born through a normal vaginal delivery or a C-section.